Oxyfuel Combustion – Experimental Investigation of Sorption Effects on Coal Char. (May 2017) - Wedler, C.; Seibel, C.; Richter, M.; Fieback, T.M.; Span, R.
Abstract: The DFG Collaborative Research Center SFB/TRR129 "Oxyflame" is devoted to developing a fundamental understanding of effects relevant for the combustion of solid fuels in oxyfuel atmospheres. 17 complementary research projects at RWTH Aachen, TU Darmstadt, and Ruhr-Universität Bochum both numerically and experimentally deal with various aspects on scales reaching from single particles to complete combustion chambers. As part of this framework, this project experimentally addresses the impact of sorption effects on the surface of chars and of the diffusion into pores. Since the adsorption of different components of oxyfuel atmospheres is selective and since the composition of a boundary layer on the surface of char particles is relevant for equilibria and dynamics of heterogeneous reactions during char burnout, selectivities of sorption and effective diffusion coefficients are considered important inputs for the advancement of particle-burnout models. This paper describes results of measurements of the sorption of main components of oxyfuel atmospheres (CO2 and O2 ) on char particles. Selectivities are derived from the experimental results. The extrapolation of selectivities to higher temperatures, which is essential for their application in burnout models, is discussed.